Cutaneous infection with Mycobacterium chelonae in a patient with multiple sclerosis - Morteza Masoumi; Fatemeh Sakhaee; Morteza Ghazanfari Jajin; Seyed Davar Siadat; Abolfazl Fateh (IDCases)
Cutaneous infections caused by Mycobacterium chelonae can present with a variety of clinical symptoms, depending on the patient's immune status. Here, we report a case involving a 46-year-old woman with multiple sclerosis who developed a cutaneous infection caused by M. chelonae. The initial presentation included skin discoloration on her right wrist, which progressed to a granuloma. Following surgical intervention, the infection led to tissue atrophy and the formation of a deep cavity at the site. Upon identification of the causative pathogen, a treatment regimen consisting of clarithromycin and moxifloxacin was initiated and continued for seven months. The patient showed signs of recovery, with the swelling and deep cavity resolving; however, some redness at the site persists. The patient remains under treatment.